Representations of hands in the Florentine Codex by Bernardino de Sahagún (ca 1499–1590). - Roith, Christian (Paedagogica Historica)
One of the most outstanding gatherers of information about the culture of the pre-Colombian Mexica of Nahua, also known as the Aztecs, was the Franciscan monk Bernardino de Sahagún, who compiled his findings in 12 books with the title General History of the Things of New Spain between 1540 and 1585. The so-called Codex is a complex document which offers a variety of information about Mexica culture in Nahuatl, Spanish, and Latin, containing also pictographical images and ornaments. This study offers iconographic interpretations of the Codex’s illustrations and especially focuses on the representations of hands and gestures, preferentially in contexts related to birth, upbringing, and education. A thorough analysis of the diverse text bodies reveals certain patterns of the transculturation process which took place in Spanish-colonised America in the sixteenth century. Furthermore, the interpretation of the material contributes to the ongoing discussion about Sahagún’s role in this process, highlighting that his use of early ethnographic-like methods was motivated by the objective to create a tool which made the conversion of the indigenous population to Catholicism, their submission and exploitation by the Spanish conquerors easier and arguing that his classification as an early ethnographer by some researchers is not correct.